ปัจจัยคัดสรรที่สัมพันธ์กับการอาสาสมัครของนิสิตปริญญาตรีจุฬาลงกรณ์มหาวิทยาลัย - ณัฐกุล อาชวกุลเทพ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purpose of this research study was to examine selected factors related to volunteerism in undergraduate students. Participants were 360 undergraduates, aged 17-24, from Chulalongkorn University. Participants were divided into 2 groups of 180 each based on their volunteerism. For those with volunteer engagement, they conducted 30 or more hours of volunteer activities during the past three months. For those without such engagement, they did not involve in any volunteer activities during that period. Independent variables were factors relevant to functions served by volunteerism, perceived behavioral control and factors relevant to prosocial personality. Research instruments were personal data questionnaire, Volunteer Functions Inventory, Perceived Behavioral Control Questionnaire, and Prosocial Personality Battery. Data were analyzed using Logistic Regression Analysis. Results demonstrated that all dependent variables of the logistic regression equation mutually explain 32.8% (R2CS = .328) of the variation. Two factors significantly related to volunteerism were the "understanding" function of volunteerism (p < .001) and perceived behavioral control (p < .001). The logistic regression equation could correctly predict volunteerism in these undergraduates with the accuracy of 77.2%.